Ventajas competitivas y desarrollo metropolitano. El caso del sistema manufacturero turinés = Competitive advantages and metropolitan development. The case of the Turin manufacturing system - Conti, Sergio (Polígonos. Revista de Geografía, 1999)
Este artículo plantea el problema de la competitividad local/regional en la era de la globalización económica contextualizado en el ámbito del debate abierto en la ciencia geográfica y la ciencia social en general. Se presta especial atención en buscar un nexo claro con el fenómeno típico de la economía contemporánea, en la que se observa, de un lado, una creciente desindustrialización de la economía occidental, y de otro lado, la búsqueda paralela de actividad y actores dentro de su propio ámbito de referencia y acción. Este cuadro dialéctico y contradictorio se ilustra de forma empírica con la referencia al caso de la región manufacturera de Turín, un área altamente industrializada que ha representado en el siglo que termina uno de los modelos más notables de organización fordista del trabajo, centrado en la producción automovilística. La transición hacia una economía post-fordista muestra en particular la ruptura con aquella lógica organizativa y la afirmación de nuevos sistemas productivos que reclaman, consiguientemente, nuevos modos de conocimiento y políticas. In this article, the problem of local/regional competitiveness in the era of the globalization of economic processes is first contextualised in the framework of the current debate in the geographical and social sciences in general. Particular care will be taken to seek out a link as clear as possible with the phenomena typical of the contemporary economy, in which we observe, on the one hand, the growing deindustrialisation of the Western economies and, on the other, a parallel rooting of activities and actors in their respective frameworks of reference and action. This dialectical and contradictory framework will then be clarified empirically with reference to the case of Turin’s manufacturing region, a highly industrialised area which in the century that has just finished represented one of the most well-known models of Fordist organisation of labour, centred on the car industry. The transition towards a post-Fordist economy shows in particular the profound break with those organisational approaches and the rise of new production clusters, and underlines the consequent need for new knowledge and policies.